Quadratic Equations Class 10 Exe- 5A RS Aggarwal Goyal Brothers ICSE Maths Solutions

Quadratic Equations Class 10 Exe- 5A RS Aggarwal Goyal Brothers ICSE Maths Solutions Ch-5. Step by step solutions of questions related root of equation  and method of factorization with zero product rule as latest prescribe guideline for upcoming exam. Visit official Website CISCE for detail information about ICSE Board Class-10.

Quadratic Equations Class 10 Exe- 5A RS Aggarwal Goyal Brothers ICSE Maths Solutions

Quadratic Equations Class 10 Exe- 5A RS Aggarwal Goyal Brothers ICSE Maths Solutions Ch-5

Board ICSE
Subject Maths
Class 10th
Chapter-5 Quadratic Equations
Writer/ Book RS Aggarwal
Topics Solution of Exe-5A Questions
Academic Session 2024-2025

Solution of Exe-5A Questions

Quadratic Equations Class 10 RS Aggarwal Goyal Brothers ICSE Maths Solutions Ch-5

Page- 52,53

Exercise- 5A

( Root of Quadratic Equations and method of factorization with zero product rule )

Que-1: Find which of the following are the solution of the equation  6x²-x-2 =0 ?

(i) 1/2   (ii) -1/2   (iii) 2/3

Solution- 6x²−x−2 = 0
Here, a = 6, b = −1, c = 2
x = [−b±√b²−4ac]/2a
= [−(−1)±√(−1)²−4(6)(−2)]/2(6)
= [1±√1+48]/12
= [1±√49]/12
= [1±7]/12
x = (1+7)/12 and x = (1−7)/12
∴ x = 2/3 and x = −1/2
So, 2/3 and -1/2 are the solution of 6x²−x−2 = 0
Que-2: Determine whether x = -1/3 and x = 2/3 are the solution of the equation 9x²-3x-2 = 0.
Solution- Given equation is 9x2 – 3x – 2 = 0; and x = -1/3, or 𝑥 = 2/3
Substitute x = -1/3 in the L.H.S.
L.H.S. = 9(-1/3)²-3×(-1/3)-2
= 9×1/9+1-2
= 2 – 2
= 0
= R.H.S.
Hence, x = -1/3 is a solution of the equation.

Again now put x = 2/3
L.H.S. = 9(2/3)²-3(2/3)-2
= 9×4/9-2-2
= 4 – 4
= 0
= R.H.S.
Hence, x = 2/3 is a solution of the equation.

Solve the following equations by factorization :

Que-3: 16x² = 25
Solution- 16x² = 25
x² = 25/16
x = √(25/16)
x = ±5/4
x = 5/4 or -5/4 Ans.
Que-4: x²+2x = 24

Solution- x²+2x = 24
x²+2x-24 = 0
x²+6x-4x+24 = 0
x(x+6)-4(x+6) = 0
(x-4)(x+6) = 0
x-4 = 0 and x+6 = 0
x = 4,-6 Ans.

Que-5: x²-x = 156

Solution- x²-x = 156
x²-x-156 = 0
x²+12x-13x-156 = 0
x(x+12)-13(x+12) = 0
(x+12)(x-13) = 0
x+12 = 0 and x-13 = 0
x = -12,13 Ans.

Que-6: x²-11x = 42

Solution- x²-11x = 42
x²-11x-42 = 0
x²+3x-14x-42 = 0
x(x+3)-14(x+3) = 0
(x+3)(x-14) = 0
x+3 = 0 and x-14 = 0
x = -3,14 Ans.

Que-7: x²-7x+10 = 0

Solution- x²-7x+10 = 0
x²-2x-5x+10 = 0
x(x-2)-5(x-2) = 0
(x-2)(x-5) = 0
x-2 =0 and x-5 = 0
x = 2,5 Ans.

Que-8: x²+18x = 40

Solution- x²+18x = 40
x²+8x-40 = 0
x²+20x-2x-40 = 0
x(x+20)-2(x+20)
(x-2)(x+20) = 0
x-2 = 0 and x+20 = 0
x = 2,-20 Ans.

Que-9: x²+17 = 18x

Solution- x²+17 = 18x
x²-18x+17 = 0
x²-17x-x+17 = 0
x(x-17)-1(x-17) = 0
(x-17)(x-1) = 0
x-17 = 0 and x-1 = 0
x = 17,1 Ans.

Que-10: 3x² = 5x

Solution- 3x² = 5x
3x²-5x = 0
x(3x-5) = 0
x = 0 and (3x-5) = 0
x = 0, 5/3 Ans.

Que-11: (x+3)(x-3) = 27

Solution- (x+3)(x-3) = 27
x²-3x+3x-9 = 27
x² = 27+9
x² = 36
x = √36
x = ±6
x = -6,6 Ans.

Que-12: x²-30x+216 = 0

Solution- x²-30x+216 = 0
x²-18x-12x+216 = 0
x(x-18)-12(x-18) = 0
(x-12)(x-18) = 0
(x-12) = 0  and (x-18) = 0
x = 12,18 Ans.

Que-13: 12x²+29x+14 = 0

Solution- 12x²+29x+14 = 0
12x²+8x+21x+14 = 0
4x(3x+2)+7(3x+2) = 0
(4x+7)(3x+2) = 0
(4x+7) = 0  and  (3x+2) = 0
x = -7/4, -2/3 Ans.

Que-14: 2x²-7x = 39

Solution- 2x²-7x = 39
2x²-7x-39 = 0
2x²+6x-13x-39 = 0
2x(x+3)-13(x+3) = 0
(2x-13)(x+13) = 0
(2x-13) = 0  and  (x+13) = 0
x = 13/2, -3 Ans.

Que-15: 10x² = 9x+7

Solution- 10x² = 9x+7
10x²-9x-7 = 0
10x²+5x-14x-7 = 0
5x(2x+1)-7(2x+1) = 0
(5x-7)(2x+1) = 0
(5x-7) = 0  and  (2x+1) = 0
x = 7/5, -1/2 Ans.

Que-16: 15x²-28 = x

Solution- 15x²-28 = x
15x²-x-28 = 0
15x²+20x-21x-28 = 0
5x(3x+4)-7(3x+4) = 0
(5x-7)(3x+4) = 0
(5x-7) = 0  and  (3x+4) = 0
x = 7/5, -4/3 Ans.

Que-17: 8x²+15 = 26x

Solution- 8x²+15 = 26x
8x²-26x+15 = 0
8x²-6x-20x+15 = 0
2x(4x-3)-5(4x-3) = 0
(2x-5)(4x-3) = 0
(2x-5) = 0  and  (4x-3) = 0
x = 5/2, 3/4 Ans.

Que-18: 3x²+8 = 10x

Solution- 3x²+8 = 10x
3x²-10x+8 = 0
3x²-6x-4x+8 = 0
3x(x-2)-4(x-2) = 0
(3x-4)(x-2) = 0
(3x-4) = 0  and  (x-2) = 0
x = 4/3, 2 Ans. 

Que-19: x(6x-11) = 35

Solution- x(6x-11) = 35
6x²-11x-35 = 0
6x²+10x-21x-35 = 0
2x(3x+5)-7(3x+5) = 0
(2x-7)(3x+5) = 0
(2x-7) = 0  and  (3x+5) = 0
x = 7/2, -5/3 Ans.

Que-20: 6x(3x-7) = 7(7-3x)

Solution- 6x(3x-7) = 7(7-3x)
18x²-42x = 49-21x
18x²-42x+21x-49 = 0
6x(3x-7)+7(3x-7) = 0
(6x+7)(3x-7) = 0
(6x+7) = 0  and  (3x-7) = 0
x = -7/6, 7/3 Ans.

Que-21: 2x²-9x+10 = 0, when (i) x ∈ N   (ii) x ∈ Q

Solution- 2x²-9x+10 = 0
2x²-4x-5x+10 = 0
2x(x-2)-5(x-2) = 0
(2x-5)(x-2) = 0
(2x-5) = 0  and  (x-2) =
x = 2, 5/2
(i) x ∈ N
x = 2 Ans.
(ii) x ∈ Q
x = 2, 5/2 Ans.

Que-22: 4x²-9x-100 = 0, when x ∈ Q

Solution- 4x²-9x-100 = 0
4x²+16x-25x-100 = 0
4x(x+4)-25(x+4) = 0
(4x-25)(x+4) = 0
(4x-25) = 0  and  (x+4) = 0
x = 25/4, -4
when x ∈ Q
x = 25/4, -4 Ans.

Que-23: 3x²+11x+10 = 0, when x ∈ I

Solution- 3x²+11x+10 = 0
3x²+6x+5x+10 = 0
3x(x+2)+5(x+2) = 0
(3x+5)(x+2) = 0
(3x+5) = 0  and  (x+2) = 0
x = -5/3, -2
when x ∈ I
x = -2 Ans.

Que-24: x+(1/x) = 3*(1/3), x ≠ 0

Solution- x+(1/x) = 3*(1/3)
(x²+1)/x = 10/3
3x²+3 = 10x
3x²-10x+3 = 0
3x²-9x-x+3 = 0
3x(x-3)-1(x-3) = 0
(3x-1)(x-3) = 0
(3x-1) = 0  and  (x-3) = 0
x = 1/3, 3 Ans

Que-25: 5x-(35/x) = 18

Solution- 5x-(35/x) = 18
(5x²-35)/x = 18
5x²-35 = 18x
5x²-18x-35 = 0
5x²+7x-25x-35 = 0
x(5x+7)-5(5x+7) = 0
(x-5)(5x+7) = 0
(x-5) = 0  and  (5x+7) = 0
x = 5, -7/5 Ans.

Que-26: 10x-(1/x) = 3

Solution- 10x-(1/x) = 3
(10x²-1)/x = 3
10x²-1 = 3x
10x²-3x-1 = 0
10x²+2x-5x-1 = 0
2x(5x+1)-1(5x+1) = 0
(2x-1)(5x+1) = 0
(2x-1) = 0  and  (5x+1) = 0
x = 1/2, -1/5 Ans.

Que-27: 3a²x²+8abx+4b² = 0, a ≠ 0

Solution-In 3a²x²+8abx+4b² = 0
Roots are  [−b±√(b²−4ac)]/2a
Roots are = [−8ab±√[{(8ab)²−4×3a²×4b²}]/2×3a²
Therefore, [−8ab±√64a²b² − 48a²b²]/6a²
⇒ [−8ab±4ab]/6a²
If  [−8ab − 4ab]/6a² = [−12ab]/6a² = −2b/a
Or [−8ab + 4ab]/6a² = [−4ab]/6a² = −2b/3a
Then roots are −2b/a and −2b/3a Ans.

Que-28: 4x²-4ax+(a²-b²) = 0, where a,b ∈ R

Solution-  4x– 4ax + (a2 – b2) = 0 where a , b ∈ R
⇒ 4x2 – {2(a + b)x + 2(a – b)x} + a2 – b2 = 0
⇒ {4x2 – 2(a + b)x} – {2(a – b)x – (a2 – b2)} = 0
⇒ 2x{2x – (a + b)} – (a – b) {2x – (a + b)} = 0
⇒ {2x – (a + b)} {2x – (a – b)} = 0
⇒ 2x – (a + b) = 0
or
2x – (a – b) = 0
x = (a+b)/2   or   x = (a-b)/2 Ans.

Que-29: 5x²-12x-9 = 0, when (i) x ∈ I   (ii) x ∈ Q

Solution- 5x²-12x-9 = 0
5x²+3x-15x-9 = 0
x(5x+3)-3(5x+3) = 0
(x-3)(5x+3) = 0
(x-3) = 0  and  (5x+3) = 0
x = 3, -3/5
(i) when x ∈ I
x = 3 Ans.
(ii) when x ∈ Q
x = 3, -3/5 Ans. 

Que-30: 2x²-11x+15 = 0, when (i) x ∈ N   (ii) x ∈ I

Solution- 2x²-11x+15 = 0
2x²-6x-5x+15 = 0
2x(x-3)-5(x-3) = 0
(2x-5)(x-3) = 0
(2x-5) = 0  and  (x-3) = 0
x = 5/2, 3
(i) x ∈ N
x = 3 Ans.
(ii) x ∈ I
x = 3 Ans. 

Que-31: √3x²+11x+6√3 = 0

Solution-  √3x² + 11x + 6√3 = 0
⇒ √3x² + 9x + 2x + 6√3 = 0
⇒ √3x(x + 3√3) + 2(x + 3√3) = 0
⇒ (x + 3√3) (√3x + 2) = 0
⇒ (√3x + 2) = 0, (x + 3√3) = 0
⇒ x = -2/√3, x = -3√3  Ans.

Que-32: 2√5x²-3x-√5 = 0

Solution-2√5x²−3x−√5 = 0
⇒ 2√5x²+2x−5x-√5 = 0
⇒ 2x(√5x+1)−√5(√5x+1)
⇒(√5x+1)(2x−√5) = 0
⇒√5x+1 = 0  or  2x−√5 = 10
⇒x = −1√5 or x = √5/2 Ans.

Que-33: x²-(1+√2)x+√2 = 0

Solution- x²-(1+√2)x+√2 = 0
x²-x-√2x+√2 = 0
x(x-1)√2(x-1) = 0
(x-1)(x-√2) = 0
(x-1) = 0  or  (x-√2) = 0
x = 1, √2 Ans.

Que-34: (x+1)/(x-1) = (3x-7)/(2x-5)

Solution- (x+1)/(x-1) = (3x-7)/(2x-5)
After cross multiplying , we get
(x+1) (2x-5) = (3x-7) (x-1)
2x2 -3x -5 = 3x2 – 10x  + 7
x²- 7x + 12 = 0
(x-4) ( x-3 ) = 0
x = 4 or x = 3 Ans.

Que-35: (3x+1)/(7x+1) = (5x+1)/(7x+5)

Solution- (3x+1)/(7x+1) = (5x+1)/(7x+5)
(3x+1)(7x+5) = (5x+1)(7x+1)
21x²+15x+7x+5 = 35x²+5x+7x+1
35x²-21x²+12x-22x+1-5 = 0
14x²-10x-4 = 0
7x²-5x-2 = 0
7x²+2x-7x-2 = 0
x(7x+2)-1(7x+2) = 0
(7x+2)(x-1) = 0
(7x+2) = 0  or  (x-1) = 0
x = -2/7, 1 Ans.

Que-36: 5/(2x+1) + 6/(x+1) = 3

Solution- 5/(2x+1) + 6/(x+1) = 3
[5x+5+12x+6]/[(2x+1)(x+1)] = 3
17x+11 = (3x+3)(2x+1)
17x+11 = 6x²+3x+6x+3
17x+11 = 6x²+9x+3
6x²−8x−8 = 0
6x²−12x+4x−8 = 0
6x(x−2)+4(x−2) = 0
(x−2)(6x+4) = 0
x = 2,−4/6
x = 2, -2/3 Ans.

Que-37: 2x/(x-4) + (2x-5)/(x-3) = 25/3

Solution- 2x/(x-4) + (2x-5)/(x-3) = 25/3
6x/(x-4) + (6x-15)/(x-3) = 25
[6x(x-3) + (6x-15)(x-4)]/[(x-3)(x-4)] = 25
6x²-18x+6x²-24x-15x+60 = 25(x-3)(x-4)
12x²-32x+60 = 25(x²-4x-3x+12)
12x²-32x+60 = 25x²-175x+300
25x²-12x²-175x+32x+300-60 = 0
13x²-118x+240 = 0
x²-118x/13+240/13 = 0
x²-6x-(40x/13)+(240/13) = 0
x(x-6)-(40/13)(x-6) = 0
(x-6)(x-40/13) = 0
x = 6, 40/13 Ans.

Que-38: (x+3)/(x-2) – (1-x)/x = 4*(1/4)

Solution-Consider the given equation.
(x+3)/(x−2) − (1−x)/x = 4*(1/4)
[x²+3x−x+x²+2−2x]/(x²−2x) = 17/4
4(2x²+2) = 17(x²−2x)
8x²+8 = 17x²−34x
9x²−34x−8 = 0
9x²+2x-36x-8 = 0
x(9x+2)-4(9x+2) = 0
(x-4)(9x+2) = 0
x = 4, −2/9 Ans.

Que-39: 1/(x-2) + 2/(x-1) = 6/x

Solution- 1/(x−2)+2/(x−1) = 6/x
= [x−1+2x−4]/[(x−2)(x−1)] = 6/x
= x(3x−5) = 6(x−2)(x−1)
= 3x²−5x = 6(x²−x−2x+2)
= 3x²−5x = 6x²−18x+12
= 13x−3x²−12 = 0
= 3x²−13x+12 = 0
= 3x²−4x−9x+12 = 0
= x(3x−4)−3(3x−4) = 0
(3x−4)(x−3)
so, x = 3 or x = 4/3 Ans.

Que-40: 2[x/(x+1)]² – 5[x/(x+1)] + 2 = 0, x ≠ -1

Solution- 2[x/(x+1)]² – 5[x/(x+1)] + 2 = 0
Let (x/(x+1)) = y
2y²-5y+2 = 0
2y²-4y-y+2 = 0
2y(y-2)-1(y-2) = 0
(2y-1)(y-2) = 0
(2y-1) = 0  or  (y-2) = 0
y = 1/2  or  y = 2
Put the value of y from the above equation
x/(x+1) = 1/2  or  x/(x+1) = 2
2x = x+1  or  x = 2x+2
2x-x = 1  or  2x-x = -2
x = 1  or  x = -2 Ans.

Que-41: 5(3x+1)² + 6(3x+1) – 8 = 0

Solution- 5(9x²+1+6x) + 18x+6 – 8 = 0
45x²+5+30x+18x-2 = 0
45x²+48x+3 = 0
45x²+45x+3x+3 = 0
45x(x+1)+3(x+1) = 0
(45x+3)(x+1) = 0
x = -1, -3/45
x = -1, -1/15 Ans.

Que-42: √(x+15) = (x+3)

Solution- Squaring on both sides
x + 15 = (x + 3)2
⇒ x2 + 6x + 9 – x – 15 = 0
⇒ x+ 5x – 6 = 0
⇒ x2 + 6x – x – 6 = 0
⇒ x(x + 6) –1(x + 6) = 0
⇒ (x + 6)(x – 1) = 0
Either x + 6 = 0,
then x = -6
or
x – 1 = 0,
then x = 1
∴ x = –6, 1
x = -6 is not a root
So, x = 1 Ans.

Que-43: √(2x+9) = (13-x) 

Solution-√(2x+9) = 13−x
Squaring both sides
2x+9 = (13−x)²
2x+9 = 169−26x+x²
x²−28x−160 = 0
x²−20x−8x−160 = 0
x(x-20) -8(x-20)
(x-8)(x-20)
So, x = 8 and 20
x = 20 is not a root 
So, x = 8 Ans.

Que-44: √(3x²-2) = (2x-1)

Solution- On squaring both sides, we get
3x2 – 2 = 4x2 + 1 – 4x
⇒ -x2 + 4x – 3 = 0
⇒ x2 – 4x + 3 = 0
⇒ x2 – 3x – x + 3 = 0
⇒ x(x – 3) -1(x – 3) = 0
⇒ (x – 3) (x – 1) = 0
⇒ x = 3 or x = 1
Hence, the solutions are [3, 1] Ans.

Que-45: √(3x²+x+5) = (x-3)

Solution-√(3x²+x+5) = (x-3)
Given equation:
3x²+x+5 = (x−3)²
⇒3x²+x+5 = x²−6x+9
⇒2x²+7x−4 = 0
⇒(x+4)(2x−1) = 0
⇒x = −4, 1/2 Ans.

Que-46: Find the quadratic equation whose solution set is :

(i) {2.-3}   (ii) {-3,2/5}    (iii) {2/5,-1/2}

Solution- (i)  Since solution set is {2,-3)
⇒ x = 2 or x = -3
⇒ x – 2 = 0 or x + 3 = 0
⇒(x – 2)(x + 3) = 0
⇒ x2 + 3x – 2x – 6 = 0
⇒ x2 + x – 6 = 0 which is the required equation.

(ii) Since solution set is {-3,2/5}
x = -3  or  x = 2/5
x + 3 = 0 Or 5x – 2 = 0
⟹ (x + 3) (5x – 2) = 0
5x²-2x+15x-6 = 0
5x²+13x-6 = 0 is the required solution.

(iii) Since solution set is {2/5,-1/2}
x = 2/5  or  x = -1/2
5x-2 = 0  or  2x+1 = 0
(5x-2)(2x+1) = 0
10x²+5x-4x-2 = 0
10x² +x-2 = 0 is the required solution.

Que-47: Find the value of k for which x = 3 is a solution of the quadratic equation  (k+2)x²-kx+6 = 0. Thus, find the other root of the equation.

Solution-  Given : (k+2)x²−kx+6 = 0
Putting x = 3
(k+2)×9−k×3+6 = 0
9k+18−3k+6 = 0
6k = −24
k = −4 Ans.
Putting k = −4 in given equation
−2x²+4x+6 = 0
x²−2x−3 = 0
x²−3x+x−3 = 0
x(x−3)+1(x−3) = 0
(x+1)(x−3) = 0
x+1 = 0 or x−3 = 0
x = −1 or x = 3
Other root of the equation, x = −1 Ans.

–: End of  Quadratic Equations Class 10 Exe- 5A RS Aggarwal Goyal ICSE Solutions  :–

Return to :–  RS Aggarwal ICSE Class 10 Solutions Goyal Brothers

Thanks

Please, Share with your friends

Leave a Comment

This site uses Akismet to reduce spam. Learn how your comment data is processed.